Regulating franchise operations in South Africa : a study of the existing legal framework with suggestions for reform. - Woker, Tanya Ann (Rhodes University, Faculty of Law, Law, 2009)
This thesis analyses the existing legal framework that applies to franchising in South Africa today. The study begins with an examination of the history and nature of the franchise contract, focusing particularly on the nature of the franchise relationship. This study is undertaken in order to substantiate the argument that franchising is a unique method of doing business. There is a need therefore to recognise that the franchise contract is a special contract in its own right, just like contracts of sale, lease, insurance and suretyship. The study then goes on to examine the problems which are experienced in the sector, as well as the law which must provide solutions to these problems. The research will show that in a modern commercial world the existing legal framework, especially the common law, cannot adequately deal with many of these problems. The complex relationship between franchising and competition law is also explored. A common thread that emerges from franchise disputes is the lack of protection afforded to the interests of franchisees. Franchisees tend to be at the mercy of economically stronger franchisors, hence the belief that there is a need for a stronger regulatory framework. The study then shifts to proposals for reform. In 2000 the Department of Trade and Industry (DTI) established the Franchise Steering Committee in conjunction with the Franchise Association of South Africa (FASA) to review the regulatory environment. This Committee drafted franchise legislation which aimed to bring the regulation of the sector under the control of the DTI. This legislation has not been implemented and the DTI has changed its strategy. Instead of dealing with franchising independently, franchising will fall within the scope of consumer protection legislation. Both the consumer protection legislation and the legislation proposed by the Franchise Steering Committee are thoroughly examined and explained. Shortcomings in the proposals are highlighted and an alternative approach is recommended. It is proposed that franchise-specific legislation should be introduced but that this legislation should establish a system of co-regulation between the government and the franchise sector.
Keywords: Franchise Association of Southern Africa; Franchises (Retail trade) -- Law and legislation -- South Africa; South Africa. Dept. of Trade and Industry; Common law -- South Africa; Commercial law -- South Africa